Hexyl dithiafulvalene (HDT) substituted bipyridine ancillary ligands for panchromatic sensitization. (15th September 2021) - Venkateswarlu, Derangula; Swetha, T.; Choutipalli, Venkata Surya Kumar; Subramanian, Venkatesan; Singh, Surya Prakash
Graphical abstract: Highlights: The Hexyl dithiafulvalene (HDT) based sensitizer has been synthesized and studied influence of the ancillary ligand on the photo-physical performance. We have observed the panchromatic absorption (250-900 nm) in TER-HDT sensitizer and may lead to the high power conversion efficiency. Theoretical studies are performed using DFT calculations. We successfully demonstrated the tuning of optical properties of sensitizer by careful tailoring of bipyridine ancillary ligands. Abstract: The device performance of the dye-sensitized solar cells (DSSCs) mainly depends on the sensitizers. Ruthenium sensitizers have played a vital role in the DSSCs to improve power conversion efficiency. However, the absorbance spectra of most Ru-sensitizers limited up to 600 nm, which maybe prohibiting further improvement of short-circuit current density (Jsc ). To address this problem, TER-HDT was designed and synthesized by incorporating hexyl dithiafulvalene (HDT)-substituted bipyridine as an ancillary ligand and [2, 2′:6′, 2′'-terpyridine]-4, 4′, 4′'-tricarboxylic acid as anchoring ligand together. The synthesized TER-HDT was systematically studied and characterized by spectroscopic (proton NMR, Mass analysis), optical (UV-absorbance and photoluminescence), electrochemical and theoretical techniques. The novel sensitizer TER-HDT absorption tailed up to 900 nm, which originated from the enhanced intermolecular charge transfer in conjunction with efficient intra and intermolecular interactions. The HOMO and LUMO energy levels TER-HDT are suitable for electron injection and regeneration which may help to achieve high efficiency.